2019
DOI: 10.3390/ijerph16234714
|View full text |Cite
|
Sign up to set email alerts
|

Associated Factors of Hypertension in Women and Men in Vietnam: A Cross-Sectional Study

Abstract: Background: Hypertension is a direct cardiovascular disease risk. It causes a heavy burden on the healthcare system globally. We aim to assess hypertension occurrence and its associated factors among women and men in Vietnam. Methods: A cross-sectional study was conducted from January to February 2019 on 2203 community-dwelling women and men aged 18 years or above. Participants’ characteristics, comorbidity, behaviors, and physical measures were evaluated. Hypertension was classified as systolic/diastolic bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…The results of this study indicated that overweight or obese people (BMI ≥ 25) were more likely to have hypertension than those with normal weight. This result was in line with previous studies indicating higher BMI was positively associated with blood pressure and the development of hypertension ( 58 62 ). Results from a meta-analysis study with 25 randomized clinical trials showed that losing one kilogram in body weight was associated with a 1.05 mmHg and 2.05 mmHg reduction in systolic and diastolic blood pressure, respectively ( 63 ).…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study indicated that overweight or obese people (BMI ≥ 25) were more likely to have hypertension than those with normal weight. This result was in line with previous studies indicating higher BMI was positively associated with blood pressure and the development of hypertension ( 58 62 ). Results from a meta-analysis study with 25 randomized clinical trials showed that losing one kilogram in body weight was associated with a 1.05 mmHg and 2.05 mmHg reduction in systolic and diastolic blood pressure, respectively ( 63 ).…”
Section: Discussionsupporting
confidence: 93%
“…A study conducted in Vietnam also found a relationship between smoking and hypertension. Men who smoked faced a higher risk of hypertension than nonsmokers, which was dose-dependent (the more cigarettes smoked per day, the higher the increase in blood pressure (Cuong et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 163 articles were screened for eligibility for inclusion. Finally, 4 articles from the structured search and 2 articles from the unstructured search were included in the final data synthesis [11][12][13][14][15][16] . The flow of the studies through the review was plotted as preferred reporting items for systematic reviews and meta-analyses flow chart (Figs.…”
Section: Flow Of Retrieved Studies Through the Reviewmentioning
confidence: 99%